Platformised Affinity Spaces: Learning communities on YouTube, Twitch and TikTok - Vermeire, Zowi; de Haan, M.J.; Sefton-Green, J.; Akkerman, S.F. (Frontline Learning Research, 2024)
Online, informal learning communities bring youth opportunities for learning that schools cannot offer. Yet, there are concerns about the impact of social media platforms’ control over online learning. We argue for a re-evaluation of what an ‘online informal learning community’ is by looking at such active communities on three platforms: YouTube, Twitch and TikTok. We do this by reconsidering Gee’s ‘affinity spaces’ and by asking: how can we understand online informal learning communities in the current sociotechnical context? We observed and analysed interactions of six learning communities on YouTube, Twitch and TikTok. Our results show that in today’s platformised online context, Gee’s concept of ‘affinity spaces’ should be reconsidered in three ways. First, platforms call for discussion about affinity spaces’ boundaries through the visibility regimes that play a part in access. Second, platforms challenge the affinity spaces’ grammar; to maintain a focus on their interest, platforms need to engage with interests provided by platform cultures. Third, a more fixated hierarchisation, informed by platforms’ focus on creators, impacts affinity spaces’ social structures. We introduce the concept of ‘platformised affinity space’ as a first step to specific dynamics that platforms introduce to online informal learning communities. We conclude that we only understand these communities when acknowledging how these dynamics are appropriated as well as resisted to achieve community goals.